PROSES PENGHUBUNG PADA VELG/RIM WELDING DENGAN METODE PENCEKAMAN HIDROLIK - ardi ardiansyah; Dian Budhi Santoso (Peneliti.net, 2023)
This research aims to reveal how to make the welding results solid and consistent. The factor that plays an important role in determining the strength of a material is the mechanical properties of the material itself. The welding process can affect the tensile strength and structure of the material. The welding process is a manufacturing process used to join metal materials and form components that meet the specifications required for the construction and manufacturing industries. This study evaluates welding techniques and focuses on improving process efficiency. Through experimentation and data analysis, Shows that optimizing parameters such as welding voltage and current, as well as material temperature, can improve the quality of welding results. Flash Butt Welding’s electric resistance welding technique is used to join metal parts by utilizing the resistance heat energy of the parts themselves. The advantage of this method is that it can combine various sizes and complex shapes of metal components, commonly used in industries such as motorcycle rims/wheels. Good quality welding results can be achieved by controlling and modifying parameters such as electric current and heat temperature.